Growth, phytochemical and antioxidant activity of Orthosiphon stamineus benth. In response to organic amendment, fertilizer and harvest date - Yap, Esther Shiau Ping (2016)
Orthosiphon stamineus have been identified by Malaysian Department of Agriculture with the potential to be developed as complementary and alternative medicine. O. stamineus acts as a diuretic agent and has nephroprotective, antifungal, antimicrobial and antipyretic properties. It contained chemical markers, such as sinensetin (SEN) and rosmarinic acid (RA), with beneficial effects on consumer’s health. Malaysian soils are predominantly kaolinitic clays and sandy due to weathering and is unsuitable for plant growth. Thus, it is important to incorporate organic soil amendments before planting to improve the soil. The objective of the first experiment was to determine the rates of soil amendments (rice husk biochar (BC): 0, 5 and 10 t/ha and chicken manure (CM): 0, 2.5 and 5 t/ha) and harvesting week (HW) that could produce the maximum yield and phytochemicals. The experiment was conducted as a potted experiment using a randomized complete block design in a three factorial arrangement of treatments with four replications and three subsamples each. There was a significant quadratic increase in plant height as harvesting time was increased, irrespective of soil amendments. Plant fresh weights were significantly affected by interactions between BC × CM × HW, whereby BC 0 t/ha and CM 5 t/ha at week 8 after transplanting gave the highest yield among all the treatments. There was a significant linear relationship between BC × HW for plant dry weight. The plant dry weight showed differences of 15%, 20% and 42% between week 6 and 8 at each BC rate. Both total phenolic and flavonoid contents were also affected by interactions between BC × CM × HW. 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity showed a significant quadratic response in the interaction between BC × HW whereby week 7 produced maximum DPPH activity. Sinensetin was significantly reduced by 63% at week 4 as compared to week 8, irrespective of soil amendments. The combination of BC 5 t/ha, CM 2.5 t/ha and HW 8 produced highest biomass yield, as HW 8 gave 36% higher yield than week 6, although SEN yield was not significantly different between week 6 and 8. The second experiment was carried out to determine the optimum fertilizer rate, FR (0, 100, 200, 300 and 400 kg/ha N) and fertilizer type, FT (plant- and animal-based) that could produce the maximum yield and phytochemicals. The selected treatment combination (BC 5 t/ha and CM 2.5 t/ha at HW 8) from the first experiment was used for soil preparation. The potted experiment was conducted using a RCBD in a two factorial arrangement of treatments with four replications and three subsamples each. Both fresh and dry weights showed a significant quadratic trend against FR, irrespective of FT applied, with optimum rates at 323 kg/ha N and 219 kg/ha N, respectively. Total flavonoid contents (TFC) and DPPH activity were significantly affected by interaction between FR × FT. DPPH activity and TFC showed a quadratic trend for plant-based fertilizer with optimum rate at 218 kg/ha N and 244 kg/ha N, respectively. Chemical markers, RA and SEN, were also affected by interaction between FT × FR. Plant-based fertilizer showed a reduction in both the chemical markers as fertilizer rates increased. However, for animal-based fertilizer, the trend was quadratic, whereby the concentrations of RA and SEN were decreased by 61% and 13%, respectively, with increasing fertilizer rate from 0 kg/ha N to 200 kg/ha N. A gradual decrease, thereafter an increased in response to fertilizer rate was seen. The results showed plant-based fertilizers at 300 kg/ha N is the optimum organic fertilizer order to achieve maximum yield and phytochemicals. In conclusion, the optimum yield of O. stamineus can be obtained by using 5 t/ha rice husk biochar and 2.5 t/ha chicken manure soil amendments, plant-based organic fertilizer of 300 kg/ha N and harvested at week 8 after transplanting.